Are Partner-Country Statistics Useful for Estimating Missing Trade Data? - Yeats, J. Alexander (The World Bank, 1999)
Because many developing countries fail to report trade statistics to the United Nations, there has been an interest in using partner-country data to fill these information gaps. The author used partner-country statistics for 30 developing countries to estimate actual (concealed) trade data and analyzed the magnitude of the resulting errors. The results indicate that partner-country data are unreliable even for estimating trade in broad aggregate product groups such as foodstuffs, fuels, or manufactures. Moreover, tests show that the reliability of partner-country statistics degenerates sharply as one moves to more finely distinguished trade categories (lower-level SITCs). Equally disturbing, about one-quarter of the partner-country comparisons take the wrong sign. That is, one country's reported free-on-board (f.o.b.) exports exceed the reported cost-insurance-freight (c.i.f.) value of partners' imports. Aside from product composition, tests show that partner-country data are equally inaccurate for estimating the direction of trade. Why are partner-country data so unreliable for approximating missing data? Evidence shows: 1) problems in reporting or processing COMTRADE data; 2) valuation differences (f.o.b. versus c.i.f.) for imports and exports; 3) problems relating to entrepot trade, or exports originating in export processing zones; 4) problems associated with exchange-rate changes; 5) intentional or unintentional misclassification of products; 6) efforts to conceal trade data for proprietary reasons; and 7) financial incentives to purposely falsify trade data. The author concludes that efforts to improve the general quality, or availability, of trade statistics using partner-country data holds little or no promise, although this information may be useful in specific cases where the trade statistics of a certain country are known to incorporate major errors.